2001
DOI: 10.1046/j.1365-2222.2001.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‐induced bronchial inflammation is associated with decreased levels of surfactant proteins A and D in a murine model of asthma

Abstract: These results indicated the involvement of pulmonary surfactant proteins in the allergic bronchial inflammation of sensitized mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 35 publications
(34 reference statements)
5
45
0
2
Order By: Relevance
“…Despite some reported increases in SP-A and SP-D levels 24 h after allergen challenge, which may well represent an innate immune defense mechanism (11,12,15,59), given our findings, we believe that as well as very short-term exposure, which has been discussed above, long-term exposure to HDM allergens would disrupt the physiological levels and functions of SP-D in the lungs, and this could have profound consequences. Consistent with this, decreased levels of SP-A and SP-D in BALF are seen in the chronic phase of allergen exposure in murine models of allergic hypersensitivity to HDM allergens (58).…”
Section: Discussionsupporting
confidence: 65%
“…Despite some reported increases in SP-A and SP-D levels 24 h after allergen challenge, which may well represent an innate immune defense mechanism (11,12,15,59), given our findings, we believe that as well as very short-term exposure, which has been discussed above, long-term exposure to HDM allergens would disrupt the physiological levels and functions of SP-D in the lungs, and this could have profound consequences. Consistent with this, decreased levels of SP-A and SP-D in BALF are seen in the chronic phase of allergen exposure in murine models of allergic hypersensitivity to HDM allergens (58).…”
Section: Discussionsupporting
confidence: 65%
“…Based on studies in murine models of allergic inflammation and in studies of patients with asthma, it has become increasingly evident that SP-A and SP-D play important regulatory roles in allergic airways diseases. Mice challenged with OVA, house dust mite (HDM), or fungi have alterations in SP-A/-D levels at the height of eosinophilia (58)(59)(60). An increase in SP-A/-D during eosinophilic inflammation is likely a key defense mechanism for eosinophil regulation: SP-D inhibits eosinophil chemotaxis, SP-A and SP-D bind eosinophils and attenuate degranulation, and SP-A suppresses IL-8 production from eosinophils (61)(62)(63).…”
Section: Asthmamentioning
confidence: 99%
“…A number of studies have used animal models to address the mechanistic issues that underlie the inverse relationship between the epidemiologies of helminth infection and allergic disease in human populations (5,61,64,65) and the immunological observations that preexisting helminth infection alters the magnitude and character of the immune responses to subsequent pathogen or antigen challenges (7,12,45). Results from studies where infection with the nematode N. brasiliensis, H. polygyrus, or Strongyloides stercoralis was superimposed upon the ovalbumin allergy model demonstrated that reductions in the responses to allergen challenge were characterized by downregulation of eotaxin production, a commensurate decrease in eosinophil infiltration, and a decrease in lung-associated IgE levels (60,64,65).…”
Section: Vol 76 2008 Nippostrongylus-induced Pulmonary Changes 3519mentioning
confidence: 99%